Effects of dietary tryptophan on the antioxidant capacity and immune response associated with TOR and TLRs/MyD88/NF-κB signaling pathways in northern snakehead, Channa argus (Cantor, 1842) - Zhang, Xin; Wang, Anran; Chang, Enhui; Han, Bei; Xu, Jie; Fu, Yu; Dong, Xiaojing; Miao, Shuyan (Frontiers in Immunology, 2023)
Dietary tryptophan (Trp) has been shown to influence fish feed intake, growth, immune response. The purpose of this study was to investigate the effect and mechanism of Trp on immune system of juvenile northern snakehead (Channa argus Cantor, 1842). A total of 540 fish (10.21 ± 0.11 g) were fed six experimental diets containing graded levels of Trp at 1.9, 3.0, 3.9, 4.8, 5.9 and 6.8 g/kg diet for 70 days, respectively. The results showed that supplementation of 1.9-4.8 g/kg Trp in diets had no effect on the hepatosomatic index (HSI) and renal index (RI), while dietary 3.9 and 4.8 g/kg Trp significantly increased spleen index (SI) of fish. Dietary 3.9, 4.8, 5.9 and 6.8 g/kg Trp enhanced the total hemocyte count (THC), the activities of total antioxidant capacity (T-AOC) and superoxide dismutase (SOD). Malondinaldehyde (MDA) levels in the blood were significantly decreased by consuming 3.9 and 4.8 g/kg Trp. Fish fed 3.0 and 3.9 g/kg Trp diets up-regulated interleukin 6 (il-6) and interleukin 8 (il-8) mRNA levels. The expression of tumor necrosis factor α (tnf-α) was highest in fish fed 3.0 g/kg Trp diet, and the expression of interleukin 1β (il-1β) was highest in fish fed 3.9 g/kg Trp diet. Dietary 4.8, 5.9 and 6.8 g/kg Trp significantly decreased il-6 and tnf-α mRNA levels in the intestine. Moreover, Trp supplementation was also beneficial to the expression of interleukin 22 (il-22). Additionally, the mRNA expression levels of target of rapamycin (tor), toll-like receptor-2 (tlr2), toll-like receptor-4 (tlr4), toll-like receptor-5 (tlr5) and myeloid differentiation primary response 88 (myd88) of intestine were significantly up-regulated in fish fed 1.9, 3.0 and 3.9 g/kg Trp diets, and down-regulated in fish fed 4.8, 5.9 and 6.8 g/kg Trp diets. Dietary 4.8 and 5.9 g/kg Trp significantly increased the expression of inhibitor of nuclear factor kappa B kinase beta subunit (ikkβ) and decreased the expression of inhibitor of kappa B (iκbα), but inhibited nuclear transcription factor kappa B (nf-κb) mRNA level. Collectively, these results indicated that dietary 4.8 g/kg Trp could improve antioxidant capacity and alleviate intestinal inflammation associated with TOR and TLRs/MyD88/NF-κB signaling pathways.